Doping of Titanium Dioxide with Zirconia for Application of Dye Sensitized Solar Cell - SYAZWAN B. ABD. RAHMAN, SYAZWAN (Universiti Teknologi Petronas, 2010)
The study on the effect of doping TiO2 with Zirconia was done by using Reflux and Impregnation synthesis method. The initial molar composition of Zr/TiO2 was prepared at 1:1, 1:0.5 and 0.5:1 ratio. The produced samples from synthesis method then dried and calcined at 600oC. The effect of varied composition was determined by characterization techniques as discussed in Chapter 4. The characterization techniques include XRD analysis, SEM analysis, BET analysis, FTIR analysis, Raman Spectroscopy analysis, XPS analysis and application on test cell. Images from SEM analysis shown that more uniform distribution of nanoparticles, with reducing pore size and smaller grain size for samples with higher content of Zirconia. XRD and Raman analysis indicated the wide distribution of the monoclinic ZrO and tetragonal TiO2 anatase phase. Higher content of Titania in the samples yield worse ceramic sinterability. FTIR result shown the reduction of hydroxyl and N-H group for the samples that has been calcined.